Indeks Sombor dari Graf Koprima Prima untuk Grup Bilangan Bulat Modulo - Abdurahim, Abdurahim; Satriyantara, Rio; Maulana, Fariz; Wardhana, I Gede Adhitya Wisnu; Robbaniyyah, Nuzla Af’idatur (JURNAL DIFERENSIAL, 2025)
The prime coprime graph of integers modulo n is an ordered pair consisting of a set of vertices (integers modulo n) and edges. Two distinct vertices are said to be adjacent if the greatest common divisor (gcd) of their orders is either 1 or a prime number. This article discusses the prime coprime graph of integers modulo n for n = pq, where p < q are prime numbers. The results of the study include the degree characteristics of the vertices and the subgraphs formed. Additionally, the Sombor index of the graph is also determined.